Perancangan Sistem Informasi Pengolahan Data Akademik Pada SMK Madani Marendal I Berbasis Web - Heni Wulandari; Suherman Suherman (Journal of Computer System and Informatics (JoSYC), 2020)
The Web Based Academic Data Processing Information System at SMK Madani Marendal I is a system that manages school data online which includes the presentation of student, teacher and staff data so that it helps the admin in managing school data quickly and accurately. In addition, web based processing of school data can be accessed at an unspecified time and place. In this system, the waterfall software development model includes Requirement Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation and Maintenance. The Web Based Academic Data Proccesing Information System at SMK Madani Marendal I uses the PHP programming language and MySQL as the database